OVERCOMING DUALISM: THE IMPORTANCE OF CONSOLIDATING LAW AND REGULATION TESTING IN INDONESIA - Wardana, Dodi Jaya (Universitas Syiah Kuala, 2024)
This article highlights the significance of unifying the testing of all laws and regulations under the authority of the Constitutional Court in Indonesia. Currently, the testing of laws and regulations is divided between two state institutions, namely the Constitutional Court and the Supreme Court, resulting in dualism in the evaluation of laws and regulations. Through a normative-juridical approach, examining existing laws and theories, this article reveals that the dualism of testing laws and regulations is a problem that needs to be addressed. The problem arises from the differences in decision outcomes between the Constitutional Court and the Supreme Court. The two institutions employ different benchmarks for material testing, with the Supreme Court relying on legislation and the Constitutional Court drawing on the 1945 Constitution of the Republic of Indonesia. The importance of unifying the testing of all laws and regulations lies in the fact that the unintegrated testing system causes confusion, creates institutional conflicts between the Constitutional Court and the Supreme Court, and results in a lack of synchronization between laws and regulations from lowest to highest. Therefore, it is essential to conduct integrated testing of all laws and regulations, with the Constitutional Court serving as the authority responsible for this task. Notably, an increase in the number of Constitutional Court judges is necessary to achieve better development of laws and regulations testing in the future.